From social media to the stage: the role of visual storytelling in creating the identity of the indie diva. The case of Florence and The Machine. - Pérez-Ordóñez, Cristina de los Ángeles; Castro-Martínez, Andrea; Torres-Martín, José Luis (My University, 2023)
Nowadays, the role played by social media in the promotion and marketing strategies of artists and bands is undeniable. There are many actor in the music industry that take advantage using these platforms to enhance their impact and influence amongst fans and consumers (Anderton et al., 2022; Haynes y Marschall, 2018). This new cultural digital capital thus becomes a significant element in the creation and success of their products, either live or recorded (Arriaga y Concha, 2020). Here, visual storytelling acquieres an important role in promoting their work as well as in building their identity. Hence, artists are increasingly concerned with their conception and promotion. This study focuses on the visual universe of Florence Wells and her band Florence and The Machine, one of today's most important indie artists, and in particular on her latest album, Dance Fever. In order to do so, a mixed methodology has been used, including documentary review and narrative and visual analysis applied to the album cover designed for social media, to the music videos of her six singles, to her digital storytelling —on Instagram, Spotify and Youtube and from March 2022 to September 2022— and to the artistic and stage design of the Dance Fever Tour. The findings suggest that her visual universe is a key feature of the transmedia strategy, creating her brand identity as a new model of woman singer: the indie diva, a global, humanist and even renaissance artist, distancing her from the traditional stereotypes of the female performer.
Keywords: Música - Marketing - Congresos; Music; Visual storytelling; Indie diva; Florence and the Machine; Visual culture